Fax machines and social surveys: Teaching an old dog new tricks - Walker, Jeffery T. (Journal of quantitative criminology, 1994)
Fax machines offer solutions to many of the disadvantages associated with other methods of administering surveys. Faxes are faster than mail methods, offer more control than personal interviews, and require fewer resources than phone surveys. Fax surveys are not without their drawbacks, however. This research note examines the issues that surround this technique of conducting such a survey and considers its suitability as a survey method of the future.